Shared and distinct brain activation patterns of acupoints HT7, ST36, and KI4: a task-based fMRI study - Liyu Hu; Liyu Hu; Jinhuan Zhang; Xiaoxiong Wu; Xingxian Huang; Xinbei Li; Xingchen Liu; Hanqing Lyu; Nan Yang; Jinping Xu; Haibo Yu (Frontiers in Neurology, 2025)
ObjectiveWe aimed to investigate the shared and distinct of brain responses to manual acupuncture at HT7, ST36, and KI4.MethodsSixteen healthy participants receiving acupuncture at HT7, 19 at ST36, and 16 at KI4. All subjects experienced deqi sensation without severe pain during the acupuncture sessions. Task-functional magnetic resonance imaging was performed to explore the common and specific brain activation networks. The activation networks were further decoded for functional characterization and analyzed for network components.ResultsWe found convergence deactivation in the left cerebellar crus II across all three acupoints. Additionally, specific patterns of deactivated brain network were observed: the left superior occipital gyrus, middle temporal gyrus, and inferior parietal lobule was predominately deactivated for the HT7, the left cerebellar Crus I and right middle occipital gyrus was primarily deactivated for the ST36, and the posterior cerebellum was mainly deactivated for the KI4. They were all involved in the default, attentional, and visual networks. In addition, the control network was also related to HT7, the limbic network to ST36, and the salient network to KI4. These functional networks were linked to spatial vision and cognition, with HT7 and ST36 also influencing emotional processing.ConclusionsAll three acupoints caused shared deactivation in the left cerebellar Crus II, highlighting it as a significant region of neural convergence in acupuncture's brain modulation. HT7 and ST36 jointly influenced emotional processing, while KI4 targeted pain-cognition pathways. These findings support “acupoint-effect specificity” and guide clinical applications.